?AFLATOXINS DETOXIFICATION IN SUNFLOWER MEAL BY AMMONIATION (Biological Sciences - PJSIR, 1995)
Ammonia has been found to reduce efficiently naturally occurring aflatoxins present in sunflower meal on pilot plant scale. One percent of ammonia detoxified 96.53 ± 2.52% of aflatoxins in 30 min at 100 ± 1°C under IO ± 0.5 psi of steam pressure. The levels of naturally occurring aflatoxins in sunflower meal ranged from 113 ug/kg to 3322 ug/kg, Not much variation was observed in the detoxification process with the increase in aflatoxins content. Result- ant detoxified product was found to be free of ammoniacal smell with an average ammoniacal nitrogen of 0.1 % and average moisture content of 9.37%. The aflatoxins detoxified sunflower meal showed no toxic effect towards egg production in layer when incorporated in the rations at an inclusion rate from 8.5 to 15%, as a vegetable source of protein. The pilot-plant process demonstrated the effective way of destroying aflatoxins in sunflower meal.